Asymmetric information in credit markets, bank leverage cycles and macroeconomic dynamics - Ansgar Rannenberg (National Bank of Belgium, 2012)
The paper adds a moral hazard problem between banks and depositors as in Gertler and Karadi (2011) to a DSGE model with a costly state verification problem between entrepreneurs and banks as in Bernanke, Gertler and Girlchrist (1999, BGG). This modification amplifies the response of the external finance premium and the overall economy to monetary policy and productivity shocks. It allows the model to match the volatility and correlation with output of the external finance premium, bank leverage, entrepreneurial leverage and other variables in US data better than a BGG-type model. A reasonably calibrated simulation of a bank balance sheet shock produces a downturn of a magnitude similar to the "Great Recession".
Keywords: E44; G21; 330; Financial accelerator; bank leverage; DSGE model; Kreditgeschäft; Unternehmensfinanzierung; Bankrechnungslegung; Schock; Asymmetrische Information; Konjunktur; Dynamisches Gleichgewicht; Theorie